2016
DOI: 10.1107/s1600576716004568
|View full text |Cite
|
Sign up to set email alerts
|

Double Bragg scattering observed in small-angle X-ray scattering from highly oriented pyrolytic graphite

Abstract: In small-angle X-ray scattering from highly oriented pyrolytic graphite, radial streak patterns are observed. The streaks change their direction with sample rotation and appear and disappear in pairs. This streak pattern can be explained by double Bragg scattering. The directions of the streaks calculated as functions of the rotation angle are in good agreement with experiment. In addition, asymmetry in the intensity of the streaks and a small deviation from the radial pattern are observed, and they can be exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 7 publications
4
16
0
Order By: Relevance
“…The two streaks labelled '1' and '2' correspond to the two solutions ' f streak1 and ' f streak2 of equation (40), respectively. (Ohmasa et al, 2016), which is consistent with the theoretical prediction È ' È 0 = À B1 À 1c = 85.2 . In the present work, the streaks can be treated as straight lines because the curvature of the streaks given in equation (40) can be neglected.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…The two streaks labelled '1' and '2' correspond to the two solutions ' f streak1 and ' f streak2 of equation (40), respectively. (Ohmasa et al, 2016), which is consistent with the theoretical prediction È ' È 0 = À B1 À 1c = 85.2 . In the present work, the streaks can be treated as straight lines because the curvature of the streaks given in equation (40) can be neglected.…”
Section: Resultssupporting
confidence: 91%
“…G 2 ' ÀG 1 . As shown in the previous article (Ohmasa et al, 2016), it is found that double Bragg scattering in the small-angle region mainly consists of ðh 1 k 1 l 1 ; h 1 k 1 l 1 Þ type scatterings (h 2 = h 1 , k 2 = k 1 , l 2 = Àl 1 ). In this case, the two reciprocal-lattice vectors are nearly the same length.…”
Section: Intensity Profile Of Double Bragg Scatteringsupporting
confidence: 57%
See 3 more Smart Citations